Pengaruh Waktu Penyangraian Bawang Tiwai Terhadap, Sifat fisik, Detak Jantung dan Tekanan Darah Responden - Hardianti, Siti; Sinaga, Umi Teresia; Rohmah, Miftakhur; Rachmawati, Maulida; Saragih, Bernatal (Faculty of Agricultural Technology, Universitas Semarang, 2024)
Tiwai onion (Eleutherine americana Merr) is a medicinal plants used as an alternative treatment which is processed into herbal drinks. This study aims to determine the effect of roasting time on physical characteristics, heart rate and blood pressure in respondents. This study was arranged using a randomized block design (RBD) with 4 treatments, namely 0 minute roasting time, 5 minute, 10 minute, and 15 minute with 3 replications. Data analysis of variance and BNT follow-up test (5% level). The results showed that the roasting time of tiwai onions on physical properties had a real influence on the insoluble components, namely the treatment of 0 minutes and 15 minutes of roasting time. In terms of sensory properties, it has a significant effect on hedonic and hedonic quality of aroma, color, and taste with a description of the aroma of tiwai onions, blackish brown color and the taste of tiwai onions. On the blood pressure and heart rate of respondents after drinking the roasted tiwai drink, it significa